EFFECT OF FOLLICLE SIZE ON NUMBER AND QUALITY OF OOCYTES IN BOVINES - PRISCILLA, K LYDIA; BALAKRISHNAN, P P (The Indian Journal of Animal Reproduction, 2011)
The 891 follicles from 166 bovine ovaries were categorized as per their size ( 8mm)to observe the effect of the follicle size on oocyte number and quality. The number of oocytes recovered from< 4mm sized follicles was significantly higher (p < 0.01 ), when compared tb the recovery rate in 4 to 8mm and> 8mm category follicles (50.16, 40.62 and 9.2 per cent). Irrespective of the size of the follicle, the yield of gradeI oocytes was significantly higher (p < 0.01) when compared to other grades. It was also observed that the qualityof oocyte and follicle size had an interactive effect
Keywords: Follicle size; Oocytes; Bovine